Formulation and in vitro and in vivo evaluation of film-coated montelukast sodium tablets using Opadry® yellow 20A82938 on an industrial scale - Zaid AN; Natour S; Qaddomi A; Abu Ghoush A (Dove Medical Press, 2013)
Abdel Naser Zaid,1 Salam Natur,2 Aiman Qaddumi,2 Abeer Abu Ghoush11Department of Pharmacy, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine; 2Pharmacare PLC, Ramallah, PalestinePurpose: The aim of this study was to formulate stable film-coated montelukast sodium (MS) tablets using Opadry® yellow 20A82938 (Montikast® tablets) and to evaluate their in vitro and in vivo release profile.Methods: MS core tablets were manufactured using a direct compression method. Opadry yellow 20A82938 aqueous coating dispersion was used as the film-coating material. Dissolution of the film-coated tablets was tested in 900 mL of 0.5% sodium lauryl sulfate solution and the bioequivalence of the tablets was tested by comparing them with a reference formulation – Singulair® tablets. In vitro–in vivo correlation was evaluated. The stability of the obtained film-coated tablets was evaluated according to International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use guidelines.Results: The efficiency of the film coating was determined by subjecting the coated tablets to gastric pH and drug release was analyzed using high-performance liquid chromatography. The coated tablets had no obvious defects. MS release met the study criterion of not less than 80% dissolved after 30 minutes in 0.5% sodium lauryl sulfate solution. Statistical comparison of the main pharmacokinetic parameters clearly indicated no significant difference between test and reference in any of the calculated pharmacokinetic parameters. Level A correlation between in vitro drug release and in vivo absorption was found to be satisfactory.Conclusion: These findings suggest that aqueous film coating with Opadry yellow 20A82938 is an easy, reproducible, and economical approach for preparing stable MS film-coated tablets without affecting the drug-release characteristics.Keywords: coating, stability, aqueous dispersion, release, bioequivalence